2012
DOI: 10.1111/j.1365-4632.2011.05154.x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of cells and cytokines in the pathogenesis of psoriasis

Abstract: Psoriasis is considered an immune chronic disease in which T cells are accepted as important. Nowadays, it is believed that psoriasis is most likely a T helper (Th)1/Th17 induced inflammatory disease. However, some other cells, such as endothelial cells, dendritic cells, monocytic cells, neutrophils, keratinocytes, and several cytokines, appear to have, at different stages of the disease, an important role in its pathogenesis. For instance, the response to psoriasis therapy is dependent not only on the inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 64 publications
4
117
2
6
Order By: Relevance
“…Firstly, this is a condition where inflammation is fundamental in its pathophysiology and depression is highly prevalent (Coimbra et al, 2012;Gladman et al, 2005;Hayes and Koo, 2010;Kurd et al, 2010;Nestle et al, 2009;Schmitt and Ford, 2007). Secondly, this population gave us the ideal opportunity to explore the effect of TNF antagonism on 5-HTT.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, this is a condition where inflammation is fundamental in its pathophysiology and depression is highly prevalent (Coimbra et al, 2012;Gladman et al, 2005;Hayes and Koo, 2010;Kurd et al, 2010;Nestle et al, 2009;Schmitt and Ford, 2007). Secondly, this population gave us the ideal opportunity to explore the effect of TNF antagonism on 5-HTT.…”
Section: Discussionmentioning
confidence: 99%
“…Mice show skin-predominant but systemic inflammation as well as the prominent neutrophilia and T cell-derived IL-17 and reversal of disease with anti-IL-17, all of which have been observed in human psoriasis (7). A hallmark of human psoriatic skin is a Th1-and Th17-biased cytokine milieu (8,9). Recently the importance of IL-17A as a key driver of psoriasis has become clear, based on IL-17-directed therapies.…”
Section: Methodsmentioning
confidence: 99%
“…Psoriasis, a primarily T cell-driven autoimmune disease, affects approximately 1% to 3% of humans (3,7). Activation and subsequent cytokine secretion by self-peptide-reactive T cells contribute to disease maintenance (8,9). Further, T cell responses in psoriasis patients are largely Th17 and Th1 biased (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant cytokines produced by the keratinocytes of psoriatic lesions, such as IL-6 and IL-8, have been shown to induce keratinocyte proliferation (11). The more recently described IL-15, IL-17, IL-19, IL-20, IL-22 and IL-23, that also are found in psoriatic lesions and which also influence keratinocyte proliferation, are mainly produced by cells of hematopoietic origin such as dendritic (DC), macrophages, lymphocytes and granulocytes (12). Studies on the role of interleukins secreted by Thl7 cells (IL-17 and IL-22) revealed a complex interaction between T cells and keratinocytes (11, 12) in several inflammatory skin pathologies including acanthosis, atopic dermatitis, cutaneous lupus erythematosus (13).…”
Section: Cytokines In Skin Inflammatory Diseasesmentioning
confidence: 99%